KAJIAN ETNOBOTANI BUDAYA NGALAKSA DI KECAMATAN RANCAKALONG KABUPATEN SUMEDANG - Yuna Islamiati; Nisrina Khairun Nisa; Restu Anugrah; Triska Rosma; Tri Cahyono (EKOLOGIA, 2020)
The Rancakalong People still hold tight the local culture. Generally, the Rancakalong people are living as farmer. This matter makes the Rancakalong people do the culture of Ngalaksa. This cultural purpose is gratitude of prosperity throught the rice harvest symbolized as Dewi Sri. The purpose of this research is to examine ethnobotany of plants that used in Ngalaksa culture at Rancakalong Sub-district. The method of this research uses descriptive-exploration with the technique of data collection is Pusposive Random Sampling and Snowball Sampling. Ngalaksa culture relates with ethnobotany studies because it uses rice (Oryza sativa L.) as the main plant and other plants such as kecombrang (Etlingera elatior (Jack) R.M.Sm), congkok (Curculigo orchioides Gaertn), cariang (Colocasia esculenta (L.) Schott) and coconut (Cocos nucifera L.). These plants are needed in large quantities and cannot be replace by other plants.